Gynecological and breast cancer risk factors and screenings in lesbian and bisexual women - Nuriye BÜYÜKKAYACI DUMAN; Fatma Yildirim (Universa Medicina, 2022)
It is estimated that individuals with lesbian, gay, bisexual, transsexual, intersexual, and other sexual tendencies make up approximately 3-12% of the world population. The proportion of lesbian and bisexual women (LBW) varies between 1-20% of all women. Studies on the subject show that risk factors for gynecological malignancies and breast cancer are more common in lesbian and bisexual women than in heterosexual women. In LBW, it is reported that obesity or high body mass index, inactivity, smoking, alcohol and substance abuse, stress, anxiety disorders, depression, and sexually transmitted diseases are more common than in heterosexual women. In addition, sexually transmitted infections (STIs) such as genital herpes, human papilloma virus (HPV) infections, bacterial vaginosis, trichomoniasis, hepatitis A, syphilis, and HIV disease, that can be transmitted by homosexual relationships, are also common in these women. It is known that genital herpes and HPV are important risk factors especially in the development of cervical cancer. In addition, breastfeeding rates and lactation periods are known to have protective effects against gynecological malignancies and lactation periods are known to have protective effects against breast cancer. This review aims to discuss gynecological malignancy and breast cancer incidence in LBW and the risk factors for these cancers according to current literature. In this context, a total of 340 articles were accessed by entering keywords related to the subject in the PubMed database and analyzed according to their titles and abstracts, while duplicates were removed. However, reviews, qualitative studies, and summaries were not included in the study. A total of 23 research articles were examined, published between 2012-2022, whose full text can be accessed through the PubMed database, investigating gynecological cancer and breast cancer risk factors and screenings in LBW.